2007
DOI: 10.1164/rccm.200608-1114oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lung Volume Reduction Surgery on Resting Pulmonary Hemodynamics in Severe Emphysema

Abstract: Rationale:To determine the effect of medical treatment versus lung volume reduction surgery (LVRS) on pulmonary hemodynamics. Methods: Three clinical centers of the National Emphysema Treatment Trial (NETT) screened patients for additional inclusion into a cardiovascular (CV) substudy. Demographics were determined, and lung function testing, six-minute-walk distance, and maximum cardiopulmonary exercise testing were done at baseline and 6 months after medical therapy or LVRS. CV substudy patients underwent rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 33 publications
4
45
0
1
Order By: Relevance
“…In addition to its immediate effects, an increased RV stroke volume induced by LVRS persists until at least 3 months after surgery [8]. LVRS has been shown to lower Ppcw without a change in pulmonary artery pressure [26][27][28]. Therefore the lowered wedge pressure may be due to reduced intrathoracic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its immediate effects, an increased RV stroke volume induced by LVRS persists until at least 3 months after surgery [8]. LVRS has been shown to lower Ppcw without a change in pulmonary artery pressure [26][27][28]. Therefore the lowered wedge pressure may be due to reduced intrathoracic pressures.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have shown conflicting results, with increases in Ppa after LVRS in one study [130] but not in others [127,128]. A recent study as part of the National Emphysema Treatment Trial has shown no significant differences in terms of P pa and PVR, 6 months after medical treatment or LVRS [129].…”
Section: Lvrs and Lung Transplantationmentioning
confidence: 98%
“…There have been few studies on pulmonary haemodynamics before and after LVRS [127][128][129]. LVRS may have adverse effects on pulmonary haemodynamics owing to the reduction of the vascular bed after the resection of lung tissue.…”
Section: Lvrs and Lung Transplantationmentioning
confidence: 99%
“…Fifty-five of 110 patients underwent baseline right heart catheterization postrehabilitation and then 6 months after randomization to medical therapy or LVRS (25). Baseline demographics and lung function were similar between groups and moderate pulmonary hypertension was present at baseline (mean Ppa, 24.8 6 4.99 mm Hg).…”
Section: Effects Of Lvrs On Pulmonary Hemodynamicsmentioning
confidence: 99%